Strengthening credibility : a leader's workbook - Kouzes, James M., 1945-; Posner, Barry Z.; Bozarth, Jane, 1961- (San Francisco, CA : Jossey-Bass, 2011)
'This workbook takes you on a personal journey toward increased credibility. Step by step, you are led to: reflect on the beliefs and values that guide your leadership behavior; examine how your actions impact the perception of you as a credible messenger; explore ways to enhance your relationship with key constituents; build energy and commitment around shared aspirations'--P. [4] of cover.
'Designed to be used as both an independent guide and a companion to ... [the authors' book], Credibility : how leaders gain and lose it, why people demand it'--P. [4] of cover.
Includes bibliographical references.
Keywords: Leadership -- Problems, exercises, etc; Executive ability -- Problems, exercises, etc; Interpersonal relations -- Problems, exercises, etc